2008
DOI: 10.1007/s10620-008-0529-y
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Carcinomatosis Attributed to Metastatic Breast Carcinoma

Abstract: A 41-year-old female suffered from epigastralgia and intermittent constipation for 10 months, and abdominal fullness and intermittent pain for 6 months, before seeking help. Double contrast barium study of the colon showed multiple indentations on the sigmoid, ascending, and proximal transverse portions with tethered adjacent mucosal outline as well as the presence of ascites compatible with peritoneal carcinomatosis. Mediolateral oblique mammogram showed a speculated mass with some intratumoral microcalcifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 10 publications
2
7
0
Order By: Relevance
“…As described in previous reports, the most common initial diagnosis in patients with peritoneal metastases without known primary tumor has been ovarian cancer [6]. Similarly, in this case the patient presented with ascites and bilateral ovarian masses, and a diagnosis of ovarian cancer was made.…”
Section: Discussionsupporting
confidence: 59%
“…As described in previous reports, the most common initial diagnosis in patients with peritoneal metastases without known primary tumor has been ovarian cancer [6]. Similarly, in this case the patient presented with ascites and bilateral ovarian masses, and a diagnosis of ovarian cancer was made.…”
Section: Discussionsupporting
confidence: 59%
“…Our study provides previously unavailable information on the treatment of women with PM from BC showing that once the correct diagnosis has been established [ 30 ], these patients can benefit from treatment and possibly argues against previous reports describing a poor prognosis. In our patients, a median 18 years (range 10–30) elapsed after BC was diagnosed and peritoneal carcinomatosis developed and accords with previous reports describing breast carcinoma as one of the most slowly growing solid tumors given that metastases may appear even decades after the initial diagnosis [ 34 , 35 ]. Of the five patients treated, four achieved long-term survival, one surviving even for 10 years with good QOL.…”
Section: Discussionsupporting
confidence: 90%
“…Systemic chemotherapy for PM improved but remains limited because of poor diffusion of the drugs into the peritoneum. This is why many authors [ 1 , 34 , 35 , 50 55 ] reported small observational series of patients with PM from various unconventional tumors treated by CRS and HIPEC (Table 2 ). This combined treatment modality has been used in peritoneal metastases from pancreatic, abdominal sarcomas, gallbladder, liver, cholangiocarcinoma, adrenal, urachal, esophageal, and kidney tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Our patient is one of the few cases, reported in the literature, of pelvic recurrence from breast cancer. Chen in 2006 and Sheen-Chen in 2008 published, respectively, a case of primary breast cancer with metastasis to ovary and omentum and a case of metastatic ovarian cancer similar to the original breast carcinoma [23,24]. Diagnosis of pelvic metastatic tumor from breast origin is not simple.…”
Section: Discussionmentioning
confidence: 99%